Bankruptcy Prediction Analysis of PT Bank Muamalat Indonesia Tbk for the Period 2015–2022 Using the Altman Z-Score and Springate Models - lutfi, Asep muhammad (Indonesian Financial Review, 2025)
This study analyzes bankruptcy prediction for PT Bank Muamalat Indonesia Tbk during 2015–2022 using the Altman Z-Score and Springate models. As Indonesia’s first Islamic bank, PT Bank Muamalat has faced challenges such as capital difficulties that could threaten its financial stability. Using descriptive quantitative methods, this research measures bankruptcy potential through financial ratios. The Z-Score model categorizes the bank as generally healthy, though some years indicate potential bankruptcy, while the Springate model consistently shows a healthy condition. The findings suggest that PT Bank Muamalat Indonesia Tbk needs to strengthen its business strategies and improve financial management to maintain stable profitability. This analysis is expected to assist investors in making informed investment decisions and to support future research in the field. Furthermore, the study contributes to developing better financial strategies and provides valuable insights for stakeholders in understanding the bank’s financial health.